Vibration measurement-based simple technique for damage detection of truss bridges: A case study. (October 2015) - Siriwardane, Sudath C.
Highlights: A simple technique is proposed to locate the damage region of railway truss bridges. The technique mainly base on variation of modal parameters respect to the position of the damage and type of the member. A case study was conducted to confirm the applicability and importance of the technique. This technique provides a warning of damage or deterioration before it is too late to attend. Abstract: The bridges experience increasing traffic volume and weight, deteriorating of components and large number of stress cycles. Therefore, assessment of the current condition of steel railway bridges becomes necessary. Most of the commonly available approaches for structural health monitoring are based on visual inspection and non-destructive testing methods. The visual inspection is unreliable as those depend on uncertainty behind inspectors and their experience. Also, the non-destructive testing methods are found to be expensive. Therefore, recent researches have noticed that dynamic modal parameters or vibration measurement-based structural health monitoring methods are economical and may also provide more realistic predictions to damage state of civil infrastructure. Therefore this paper proposes a simple technique to locate the damage region of railway truss bridges based on measured modal parameters. The technique is discussed with a case study. Initially paper describes the details of considered railway bridge. Then observations of visual inspection, material testing and in situ load testing are discussed under separate sections. Development of validated finite element model of the considered bridge is comprehensively discussed. Hence, variations of modal parameters versus position of the damage are plotted. These plots are considered as the main reference for locating the damage of the railway bridge in future periodical inspection by comparing the measured corresponding modal parameters. Finally the procedure of periodical vibration measurement and damage locating technique are clearly illustrated.